RANCANG BANGUN SISTEM INFORMASI SURAT KETERANGAN PENDAMPING IJAZAH (SKPI) FAKULTAS TEKNIK UNIVERSITAS BENGKULU MENGGUNAKAN METODE EXTREME PROGRAMMING - Soni Ayi Purnama; Tiara Eka Putri (JURNAL ILMIAH BETRIK, 2023)
A diploma Supplement (SKPI) is an obligation for universities to provide to every graduate. The process of making SKPI requires an information system in its management so that it is effective and efficient. Effective in managing SKPI by faculty management and efficiency in reporting certificate documents and SKPI supporting documents by students. The method used in the design and construction of this SKPI information system is the Extreme Programming (XP) method. The stages passed in the design using the XP method start from planning, design, coding, and testing. The design tool used in UML. The results of this research are design analysis and the website-based SKPI information system version 1.0 (one point zero), which has been tested directly by system users.